The last Brahmin prime minister - Naqvi, Saeed (New Delhi : Har-Anand Publications, 1996)
Chiefly on political events during P.V. Narasimha Rao's tenure as Prime Minister, 1991-1996.
Keywords: India -- Politics and government -- 1977-